Aggravated Damages Awards for Medical Negligence: A Need to Strengthen Medical Professionalism - Jahn Kassim, Puteri Nemie; Rosli, Muhammad Noor Firdaus (Universiti Putra Malaysia, 2021)
Aggravated Damages are awarded by the courts to compensate for injuries to feelings affecting pride and dignity, humiliation as well as mental distress. In Malaysia, this form of damages has been common in cases of assault, false imprisonment, defamation and malicious prosecution. However, the Federal Court in the case of Dr Hari Krishnan v Megat Noor Ishak [2018] 3 MLJ 281 has allowed Aggravated Damages to be awarded in medical negligence claims as the court held that such injuries are real injuries affecting a person’s body. This research will employ the Qualitative research method, namely, Content Analysis. The award of Aggravated Damages has presently become a common trend in medical negligence claims in Malaysia. The aggravating factors that have led to the award include: (i) insolent behaviour of the medical practitioner towards the patient and family members causing distress and anxiety; (ii) negative conduct displayed throughout the trial; (iii) failure to follow hospital guidelines; (iv) inaccurate information and dishonesty in documentation; (v) suppression of the patient’s medical records. Such development in the law on medical negligence is worrying and can be viewed as diminishing the core values of medical professionalism in upholding integrity, compassion, altruism, continuous improvement, and excellence in providing care to the patients. Although the working environment may be more hectic and stressful, the medical profession needs to rethink and strengthen the set of values, behaviours as well as relationships that serve as the foundation of public trust in the profession. In all eventualities, medical professionalism should continuously be upheld, preserved, and thrive regardless of the challenging times